Lateral orbitofrontal cortex activity is modulated by group membership in situations of justified and unjustified violence. (2nd November 2018) - Domínguez D, Juan F.; van Nunspeet, Félice; Gupta, Ayushi; Eres, Robert; Louis, Winnifred R.; Decety, Jean; Molenberghs, Pascal
ABSTRACT: The role of the orbitofrontal cortex (OFC) in moral decision-making is well established. However, OFC activity is highly context dependent. It is affected by the extent to which choices are morally justified and whom they concern. In the current study, we specifically focus on contextual factors and investigate the differential role of the OFC during justified and unjustified violence towards ingroup versus outgroup members. Muslims were chosen as the outgroup, as they are currently stereotypically seen as an outgroup and a potential threat by some Non-Muslims. Importantly, we also introduce a context where participants are the actual agents responsible for doing harm. During fMRI scanning, Non-Muslim participants had to decide to either shoot a Non-Muslim ( i.e ., ingroup member) or Muslim (outgroup member) depending on whether they believed the target was holding a gun or an object. Neuroimaging results showed increased activation in the lateral OFC (lOFC) in the three contrasts that were distressing: 1) during unjustifiable killing; 2) when being killed; and 3) when confronted by an outgroup member with a gun. Together, these results provide important insights into the neurocognitive mechanisms involved in intergroup violence and highlight the critical role of the lOFC in context dependent social decision-making.